Cestode parasites (Neodermata, Platyhelminthes) from Malaysian birds, with description of five new species - Mariaux, Jean; Georgiev, Boyko B. (European Journal of Taxonomy, 2020)
We studied the cestode fauna (Platyhelminthes) of forest birds in Malaysia (Selangor) collected during a field trip in 2010. Ninety birds of 37 species were examined and global prevalence of cestodes was 15.3%. Five new taxa are described: Emberizotaenia aeschlii sp. nov. (Dilepididae) from Tricholestes criniger (Blyth, 1845) (Pycnonotidae); Anonchotaenia kornyushini sp. nov. (Paruterinidae) from Trichastoma malaccense (Hartlaub, 1844) (Pellorneidae); Biuterina jensenae sp. nov. (Paruterinidae) from Chloropsis cochinchinensis (Gmelin, 1789) (Irenidae); Raillietina hymenolepidoides sp. nov. (Davaineidae) and R. mahnerti sp. nov. (Davaineidae) from Chalcophaps indica (Linnaeus, 1758) (Columbidae). Ophryocotyloides dasi Tandan & Singh, 1964 is reported from Psilopogon henricii (Temminck, 1831) (Ramphastidae). Several other taxa in Dilepididae, Davaineidae, Paruterinidae, Hymenolepididae and Mesocestoididae, either potentially new or poorly known, are also reported. The richness described from this small collection hints at the potentially huge unknown parasite diversity from wild hosts in this part of the world.